Double-edged Satire in Zamyatin's We. Issue 3 (2015) - Eichholz, Patrick
Abstract : At the end of We, our narrator retreats to an underground bathroom to complete his manuscript as Mephi revolutionaries take to the streets above. D-503's withdrawal from the fighting can easily be read as a cowardly abdication of political responsibility. In this paper, however, we will argue that D-503's retreat to his writing is the novel's true revolutionary act. To do so we will first use a Foucaultian understanding of biopower to critique the Mephi as a viable political alternative. We will then use Bakhtin's novel theory to appraise D-503's journal as the last dialogic space left between the converging OneState and Mephi, two ideologies that both come to demand the total subjugation of D-503's narratorial "I" to their monologic "we." D-503's records thus provide the final safeguard against the perfect tyranny sought by OneState and Mephi alike.